Climate change and agriculture in the Sudan: Impact pathways beyond changes in mean rainfall and temperature - Siddig, Khalid; Stepanyan, Davit; Wiebelt, Manfred; Zhu, Tingju; Grethe, Harald (International Food Policy Research Institute, 2018)
Several environmental changes have occurred in the Sudan in the past; several are ongoing; and others are projected to happen in the future. The Sudan has witnessed increases in temperature, floods, rainfall variability, and concurrent droughts. In a country where agriculture, which is mainly rainfed, is a major contributor to gross domestic product, foreign exchange earnings, and livelihoods, these changes are especially important, requiring measurement and analysis of their impact. This study not only analyzes the economy-wide impacts of climate change, but also consults national policy plans, strategies, and environmental assessments to identify interventions which may mitigate the effects. We feed climate forcing, water demand, and macro-socioeconomic trends into a modelling suite that includes models for global hydrology, river basin management, water stress, and crop growth, all connected to the International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT). The outcomes of this part of the modeling suite are annual crop yields and global food prices under various climate change scenarios until 2050. The effects of such changes on production, consumption, macroeconomic indicators, and income distribution are assessed using a single country dynamic Computable General Equilibrium (CGE) model for the Sudan. Additionally, we introduce yield variability into the CGE model based on stochastic projections of crop yields until 2050. The results of the model simulations reveal that, while the projected mean climate changes bring some good news for the Sudan, extreme negative variability costs the Sudan cumulatively between 2018 and 2050 US$ 109.5 billion in total absorption and US$ 105.5 billion in GDP relative to a historical mean climate scenario without climate change.